SGS-LTER genetic structure of metapopulations of black-tailed prairie dogs on the Central Plains Experimental Range and Pawnee National Grassland in Nunn, Colorado, USA 1997-1998 - Antolin, Michael F. (Colorado State University. Libraries, 1997)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection. Thirteen colonies of black-tailed prairie dogs were studied within a 264-km2 area of the Central Plains Experimental Range and the Pawnee National Grasslands in Weld County, Colorado. Tissue Collection, DNA Extraction, and microsatellite genotype scoring was performed.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: mammals; prairie dogs; rodents; disturbance; population dynamics; community dynamics; genetics; community ecology; populations; animals